LEGAL ESSENCE OF "TOLERABLE ACTIONS" ON FOREIGN PROPERTY (TERTIUM NON DATUR ) - Hristova, Raya (E-Journal VFU, 2024)
Reference to the concept of "tolerable actions" and the attempts through it to give or take away legal relevance to a number of facts of public life, finds an increasingly wide application in objective reality, which is why there is a need to disclose its content and the likely legal consequences of the phenomenon insofar insofar as there is a contradiction in practice regarding its legal existence
Keywords: тolerable actions; legal effects; possession; holder